Mapping the Complete Photocycle that Powers a Large Stokes Shift Red Fluorescent Protein. (22nd December 2022) - Wang, Ziyu; Zhang, Ya; Chen, Cheng; Zhu, Ruixue; Jiang, Jiaming; Weng, Tsu‐Chien; Ji, Quanjiang; Huang, Yifan; Fang, Chong; Liu, Weimin
Abstract: Large Stokes shift (LSS) red fluorescent proteins (RFPs) are highly desirable for bioimaging advances. The RFP mKeima, with coexisting cis‐ and trans ‐isomers, holds significance as an archetypal system for LSS emission due to excited‐state proton transfer (ESPT), yet the mechanisms remain elusive. We implemented femtosecond stimulated Raman spectroscopy (FSRS) and various time‐resolved electronic spectroscopies, aided by quantum calculations, to dissect the cis ‐ and trans ‐mKeima photocycle from ESPT, isomerization, to ground‐state proton transfer in solution. This work manifests the power of FSRS with global analysis to resolve Raman fingerprints of intermediate states. Importantly, the deprotonated trans ‐isomer governs LSS emission at 620 nm, while the deprotonated cis ‐isomer's 520 nm emission is weak due to an ultrafast cis ‐to‐ trans isomerization. Complementary spectroscopic techniques as a table‐top toolset are thus essential to study photochemistry in physiological environments. Abstract : Understanding the working mechanisms of red fluorescent proteins (RFPs) in aqueous solution is essential for bioimaging. We implemented a synergistic toolset (steady‐state and time‐resolved electronic and vibrational spectroscopies) and elucidated the complete photocycle that powers a large‐Stokes‐shift RFP, tracking the ultrafast excited‐state proton transfer and chromophore twists in action and also providing protein rational design principles.